Successful clipping of A Gaint Basilar Tip Aneurysm: A Case Report with Review of literature - Shrestha, Prabin; Singh, Anish M; Sah, Hemant; Baral, Bidur (Nepal Journal of Neuroscience, 2016)
Basilar tip aneurysm is the commonest aneurysm in posterior circulation. It comprises of about 5% of total aneurysms of cerebral circulation. Giant basilar tip aneurysm is rare and is technically challenging. Bigger is the aneurysm more complex is its structure leading to technical difficulty in its treatment, may it be surgical clipping or endovascular coiling. We present 50-year-old male patient presented with sudden and severe headache with altered consciousness. CT head showed sub arachnoid hemorrhage and CT angiography showed giant basilar tip aneurysm measuring more than 23 mm in length. Moreover basilar tip bifurcation and both the posterior cerebral artery arose from posterior aspect of lower part of the trunk of aneurysm. Because of the huge size and origin of the major branches from aneurysm trunk surgical clipping seemed highly risky. Patient was planned for coil embolization in India. But due to cost factor surgical clipping was planned. Successful clipping was done through right frontotemporal transtentorial approach. Small residual aneurysm was noted in the anterior lower part of aneurysm trunk which was wrapped with hemostatic agents. Complete resection of the aneurysm was done showing complete obliteration of the aneurysm. Post operatively patient was neurologically intact except ipsilateral oculomotor nerve palsy. Patient was discharged on 6th post operative day. Nepal still lacks endovascular coiling facility. Cost factor is a major hindrance for this. Surgical clipping is still the fi rst choice of treatment for any aneurysm in Nepal. There is no alternative to skill development and successful clipping for treating aneurysm in Nepal. Nepal Journal of Neuroscience 12:40-42, 2015